Efektivitas Metode Drill dalam Meningkatkan Penguasaan Mufradat Bahasa Arab Siswa Kelas 2 Salafiyyah Ula Tahfizh Ummul Quro - Jihan Aqilah Fitriah Simamora; M. Ripani Saputra (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Vocabulary mastery is an important element in Arabic language learning, but second-grade students of Salafiyyah Ula Tahfizh Ummul Quro still have difficulty remembering the vocabulary they have learned so that their learning outcomes are not optimal. This study aims to determine the effectiveness of the drill method in improving students' mastery of Arabic vocabulary. The study used a quantitative approach with a one-group pretest–posttest design. The research subjects were 19 students. Data collection techniques were carried out through pretest and posttest vocabulary mastery tests. Data were analyzed using validity tests, reliability tests, normality tests, Wilcoxon Signed Rank Tests to test differences in learning outcomes before and after treatment, and N-Gain analysis to determine the level of improvement in learning outcomes. The results showed that the average score of students increased from 57.37 in the pretest to 91.00 in the posttest. The results of the Wilcoxon Signed Rank Test showed a significance value of 0.000 (<0.05), which means there was a significant difference between the pretest and posttest results. The N-Gain analysis obtained an average score of 0.7488, which is considered high, with an effectiveness percentage of 74.88%. This finding indicates that the drill method is effective in improving students' mastery of Arabic vocabulary through repeated and targeted practice.